The effect of harvest time of ensiled whole crop field pea or faba bean on their composition and in vivo digestibility - Kuoppala, Kaisa; Lötjönen, Timo; Huuskonen, Arto; Rinne, Marketta (Scientific Agricultural Society of Finland, 2026)
This study evaluated the botanical, morphological and chemical composition of pea-wheat (PW) and faba bean-wheat (FBW) whole crop herbages at different harvest times at 2-week intervals in Northern Finland. The herbages were also ensiled in round bales and their in vivo digestibility was measured using the total faecal collection method with sheep. The grain legumes dominated in the stands so that the proportions of pea and faba bean were on average 0.912 and 0.824 (on dry matter (DM) basis). The harvest time affected the organic matter digestibility of the crops differently as it decreased for PW but increased for FBW with progressing growth. The average in vivo D-values of the silages were rather low (581 and 595 g kg-1 DM for PW and FBW, respectively). In vitro pepsin-cellulase digestibility predicted in vivo organic matter digestibility moderately well (R2=0.54), but the data set was small. Ensiled whole-crop cereal silages dominated by grain legumes showed potential as feeds for cattle.
Keywords: whole crop cereal silage; Vicia faba; Pisum sativum; in vitro digestibility; indigestible neutral detergent fibre